If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3z + 6y)(8y + -4z) = 0 Reorder the terms: (6y + 3z)(8y + -4z) = 0 Multiply (6y + 3z) * (8y + -4z) (6y * (8y + -4z) + 3z * (8y + -4z)) = 0 ((8y * 6y + -4z * 6y) + 3z * (8y + -4z)) = 0 Reorder the terms: ((-24yz + 48y2) + 3z * (8y + -4z)) = 0 ((-24yz + 48y2) + 3z * (8y + -4z)) = 0 (-24yz + 48y2 + (8y * 3z + -4z * 3z)) = 0 (-24yz + 48y2 + (24yz + -12z2)) = 0 Reorder the terms: (-24yz + 24yz + 48y2 + -12z2) = 0 Combine like terms: -24yz + 24yz = 0 (0 + 48y2 + -12z2) = 0 (48y2 + -12z2) = 0 Solving 48y2 + -12z2 = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12z2' to each side of the equation. 48y2 + -12z2 + 12z2 = 0 + 12z2 Combine like terms: -12z2 + 12z2 = 0 48y2 + 0 = 0 + 12z2 48y2 = 0 + 12z2 Remove the zero: 48y2 = 12z2 Divide each side by '48'. y2 = 0.25z2 Simplifying y2 = 0.25z2 Take the square root of each side: y = {-0.5z, 0.5z}
| 7x-9=(-9) | | (3x-5)+(5x+1)= | | -7/10m=-1327/24 | | 5(3-4x)+14x=7(2-5x) | | 9/5m-5/2m=1327/24 | | 3(6x-2)+4(1-5x)=x | | K/9-2=-11 | | -8.5-16=3*8.5+18+2*-8.5 | | ((1/21)x^(-1/21))(20-41x)=0 | | 27-9x=14 | | -4y-8=8y+100 | | -22-3x=-2x+x-3X | | -5=4x-3x | | 4w+5=5w-6 | | .5(2x+4)=3x-4 | | 4(8-x)=2x+16 | | -63+3y+8=2(5y-3)-7 | | 8n+11=10n-11 | | 2(x-5)=15x-4x | | x+(x*.0975)=4.21 | | .3x+1.4=4.2-.1x | | 4m+4=10m-62 | | -7/10m=-1324/24 | | 4+17n-3=9n+85-47 | | 100/900=85/x | | Y=-2x^3-2x^2+60x | | ax-2cx+4ay-8cy= | | 18-8-2=.5(18-2) | | -27+3*27=27+27 | | -u+106=240 | | c-3=2-3 | | 2-4-3-4=4 |